2003
DOI: 10.1002/ccd.10445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a spasmolytic cocktail to prevent radial artery spasm during coronary procedures

Abstract: Radial artery spasm is a frequent complication of the transradial approach for coronary angiography and angioplasty. Recently, we have been able to quantify spasm using the automatic pullback device. The objective of this study was to assess the efficacy of an intra-arterial vasodilating cocktail in reducing the incidence and severity of radial artery spasm. A hundred patients undergoing coronary procedures via the radial artery were divided into two groups of 50 each. Patients in group A received intra-arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 13 publications
8
99
0
10
Order By: Relevance
“…[17][18][19] Dentre outros fatores de prevenção, a utilização de várias drogas com efeito vasodilatador tem se mostrado eficaz em vários estudos 7,8,[20][21][22] , além da utilização de introdutores hidrofílicos, que promovem menor reação inflamatória tecidual local por menor trauma mecânico à parede arterial. Em estudo randomizado recente, Rathore et al 14 avaliaram 790 pacientes submetidos a intervenção coronária percutânea que utilizaram introdutores hidrofílicos e não-hidrofílicos e encontraram diminuição de cerca de 50% da incidên-cia de espasmo com a utilização dos introdutores recobertos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[17][18][19] Dentre outros fatores de prevenção, a utilização de várias drogas com efeito vasodilatador tem se mostrado eficaz em vários estudos 7,8,[20][21][22] , além da utilização de introdutores hidrofílicos, que promovem menor reação inflamatória tecidual local por menor trauma mecânico à parede arterial. Em estudo randomizado recente, Rathore et al 14 avaliaram 790 pacientes submetidos a intervenção coronária percutânea que utilizaram introdutores hidrofílicos e não-hidrofílicos e encontraram diminuição de cerca de 50% da incidên-cia de espasmo com a utilização dos introdutores recobertos.…”
Section: Discussionunclassified
“…[3][4][5] O espasmo da artéria radial é uma das complicações mais comuns da técnica, causando significante desconforto para o paciente e reduzindo a taxa de sucesso do procedimento. [6][7][8][9] O tempo prolongado do exame, a utilização de cateteres de maior diâmetro, a maior manipulação no procedimento e o maior núme-ro de cateteres utilizados estão entre as principais causas. 10 O objetivo deste estudo é avaliar se a utilização de cateteres únicos dedicados ao acesso radial poderia minimizar tais ocorrências e, consequentemente, diminuir a incidência de espasmo.…”
Section: Comparison Of a Single Dedicated Catheter And The Judkins Caunclassified
“…The incidence of RAS is not negligible and implies the need for risk factor determination before the procedure. Although previous studies have reported several RAS associated factors, radial artery pulse grading has not been investigated yet [7][8][9][10]. We hypothesised that radial artery pulse grading may predict RAS.…”
Section: Introductionmentioning
confidence: 92%
“…However, one of the major and well-defined disadvantages of the transradial approach is radial artery spasm (RAS), which causes severe discomfort and access site crossover [6][7][8]. The incidence of RAS is not negligible and implies the need for risk factor determination before the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…11 Worldwide there has been a lot of studies of spasmolytics which has shown the benefit. 4,5,6,9,11,12,13,14 Among these studies it has been recommended by Kiemeneij et al 11 that the spasm is significantly reduced by 34-14% by the use of cocktail with intra-arterial nitroglycerin and verapamil. Radial access for coronary intervention has been in practice in Nepal for last several years there has been no study regarding the different vasodilator regimen for the prevention of radial artery spasm during the procedure.…”
Section: *Corresponding Authormentioning
confidence: 99%